Carotid artery atherosclerotic profile as a predictor of the aorta atherosclerotic profile in patients with cerebrovascular events - Hueb, João Carlos [UNESP]; Bazan, Rodrigo [UNESP]; Braga, Gabriel Pereira [UNESP]; Fusco, Daniéliso Renato; Bazan, Silméia Garcia Zanati [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Karger Publishers, 2013)
Background: It is well known that the presence of atheroma of the thoracic aorta is a risk factor for cerebrovascular events. We sought to evaluate whether the presence and the morphology of atherosclerotic plaque in the carotid artery detected by duplex ultrasonography is associated with disease in the proximal aorta visualized by transesophageal echocardiogram in patients with a cerebrovascular event. Methods: We carried out a cross-sectional prospective study including 147 consecutive patients with prior stroke or transient ischemic attack (TIA). Neurological evaluations were performed by an expert neurologist using clinical and tomographic diagnostic criteria including the definition of etiology and whether the patient suffered from stroke or TIA. Transthoracic and transesophageal echocardiograms and carotid artery duplex ultrasonography were performed by the same examiner. Patients with and without plaque in the carotid artery were compared using Student's t test or the χ2 test. Regression analysis was used to determine whether the presence of plaque in the carotid artery was predictive of the presence of plaque in the proximal aorta and to analyze the relationship between the echogenicity of carotid and aortic plaques. The significance level was set at p < 0.05. Results: All 147 patients (95 men) were included in the analysis. Patients' ages ranged from 23 to 85 years (65 ± 12.4 years). Most of the patients (58.5%) were Caucasian, while 41.5% were African-Brazilian. Arterial hypertension, diabetes and tobacco use were more frequent among patients with atherosclerotic plaque in the aorta. A normal carotid intima-media thickness halved the risk of atherosclerotic plaque in the aorta [odds ratio (OR) 0.46, 95% confidence interval (CI) 0.23-0.91; p = 0.026]. The presence of carotid plaque increased the risk of aortic plaque by 70-fold (OR 73.2, 95% CI 25.6-2,018.6; p < 0.001) in univariate analysis. The absence of atherosclerotic plaque in the carotid artery reduced the risk of plaque in the aorta to almost 0 (OR 0.014, 95% CI 0.004-0.041; p < 0.001). Considering the 86 patients with both aortic and carotid plaques, the presence of hypoechoic plaque in the carotid artery was a predictor of hypoechoic plaque in the aorta (OR 10.1, 95% CI 3.3-31.2; p < 0.001). Conclusions: The carotid artery atherosclerotic profile defined by ultrasonography is a strong predictor of the atherosclerotic profile of the proximal aorta. This should be taken into consideration before referring patients with acute cerebrovascular events for transesophageal echocardiogram. © 2013 S. Karger AG, Basel.
Keywords: Aorta; Atherosclerosis; Carotid arteries; Stroke; Ultrasonography; adult; aged; aorta; aorta atherosclerosis; artery diameter; artery intima; artery media; atherosclerotic plaque; carotid artery; carotid atherosclerosis; Caucasian; cerebrovascular accident; cerebrovascular disease; echography; female; human; hypertension; major clinical study; male; neurologic examination; neurologist; patient referral; predictive value; priority journal; prospective study; Student t test; tobacco; transesophageal echocardiography; transient ischemic attack; transthoracic echocardiography